2014
DOI: 10.1093/medlaw/fwu032
|View full text |Cite
|
Sign up to set email alerts
|

One Size Fits All? On Patient Autonomy, Medical Decision-Making, and the Impact of Culture

Abstract: While both medical law and medical ethics have developed in a way that has sought to prioritise patient autonomy, it is less clear whether it has done so in a way that enhances the self-determination of patients from non-western backgrounds. In this article, we consider the desire of some patients from non-western backgrounds for family involvement in decision-making and argue that this desire is not catered for effectively in either medical law or medical ethics. We examine an alternative approach based on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 15 publications
2
58
0
2
Order By: Relevance
“…Autonomy implies the capacity to think, decide and act on one's own free initiative (British Medical Association., 2013). In the Western culture, this is highly valued by both healthcare providers and patients, who are usually well informed about this topic, which ultimately lead to gradual attenuation of medical paternalism (Gilbar & Miola, 2015;Gillon, 1994;Khoury & Khoury, 2015;Surbone, 2006;Tuckett, 2004). However, in some Middle Eastern cultures, beneficence usually precedes autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy implies the capacity to think, decide and act on one's own free initiative (British Medical Association., 2013). In the Western culture, this is highly valued by both healthcare providers and patients, who are usually well informed about this topic, which ultimately lead to gradual attenuation of medical paternalism (Gilbar & Miola, 2015;Gillon, 1994;Khoury & Khoury, 2015;Surbone, 2006;Tuckett, 2004). However, in some Middle Eastern cultures, beneficence usually precedes autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…7,16 In certain Middle Eastern, North African and South Asian societies, the family has final authority in TDM, as often the patient is inseparably linked to the family as a whole. 17 For example, the majority of cancer patients in South Korea preferred shared TDM with their family members, although it was noted that there may be disagreements between family members and patients. 7 In a study from Pakistan, family members sometimes met the physician independently and gave consent for treatment on the patient's behalf.…”
mentioning
confidence: 99%
“…Indeed, medical law in many Western countries states that, in the majority of circumstances, the patients themselves have the final decision with regards to TDM. 17 However, the cultural background of the physicians may influence their response to involving family members in the TDM process. One study conducted in the USA showed that the majority of physicians of Japanese heritage would obey a family's request not to involve the cancer patient in TDM while very few North American physicians would consent to this request.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the English legal context in healthcare, for instance, Gilbar and Miola observe that ‘the emergence of relational autonomy has not yet yielded a meaningful legal response to the impact of the patient’s cultural background on the decision-making process, thus creating difficulties for clinicians and some patients to make decisions about treatment’. 25 Similarly, McLean notes the law’s ongoing strong focus on the individual’s decision-making capacity and her individual right thereof to exercise in decision-making. 26 Despite her criticisms of the law’s extant approach, however, McLean is equally concerned that emphasising ‘the importance of inter-relatedness can result in an undue focus on the interest of others and this is evident, for example, when the decisions of pregnant women are disregarded in the interests of a future child’.…”
Section: Introductionmentioning
confidence: 99%